2003
DOI: 10.1007/s00251-003-0567-8
|View full text |Cite
|
Sign up to set email alerts
|

MHC polymorphism and disease resistance in Atlantic salmon (Salmo salar); facing pathogens with single expressed major histocompatibility class�I and class�II loci

Abstract: Few studies have yet addressed the functional aspects of MHC molecules in fish. To lay the foundation for this, we evaluated the association between disease resistance and MHC class I and class II polymorphism in Atlantic salmon. Standardized disease challenge trials were performed on a semi-wild Atlantic salmon population with subsequent MHC typing and statistical analysis. The pathogens employed were infectious salmon anaemia virus (ISAV) causing infectious salmon anaemia and the Aeromonas salmonicida bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
235
2
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(247 citation statements)
references
References 40 publications
8
235
2
2
Order By: Relevance
“…For example, disease challenge trials on Atlantic salmon confirm that polymorphism at the MHC genes are associated with increased disease resistance (Grimholt et al, 2003). Wild populations show evidence for local adaptation (de Eyto et al, 2007), and several studies indicate that MHC genes, as well as a number of linked loci, can be more powerful than neutral microsatellites in detecting population differentiation in spatially structured fish species such as salmonids (Bernatchez and Landry, 2003;Beacham et al, 2005;Hansen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, disease challenge trials on Atlantic salmon confirm that polymorphism at the MHC genes are associated with increased disease resistance (Grimholt et al, 2003). Wild populations show evidence for local adaptation (de Eyto et al, 2007), and several studies indicate that MHC genes, as well as a number of linked loci, can be more powerful than neutral microsatellites in detecting population differentiation in spatially structured fish species such as salmonids (Bernatchez and Landry, 2003;Beacham et al, 2005;Hansen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The locus is situated in the third intron of the MH IIA gene, and the extent to which the variability in the microsatellite reflects exonic variability is unknown (Stet et al, 2008). Previous attempts to estimate the variability in MHC genes using embedded micro-or minisatellites in salmonids have yielded varying results Grimholt et al, 2002Grimholt et al, , 2003Hansen et al, 2007;de Eyto et al, 2007). de Eyto et al (2007) found a one-to-one relationship between minisatellite and MH class II allelic variability; however, for MH class I, a specific microsatellite allele could be found in several different MH I alleles.…”
Section: Markers Influenced By Selectionmentioning
confidence: 99%
“…This is for example highlighted by the fact that moderate genotyperenvironment interaction was also found for rainbow trout survival during the grow-out period, as shown by the non-unity genetic correlations between environments (Vehvila¨inen et al, 2008 ;present study). Similarly, different alleles of a single gene may provide resistance against different diseases or mortality factors (Shook & Johnson, 1999 ;Grimholt et al, 2003). In fact, one pattern behind the weak correlations across life stages was that sea growout survival, not freshwater, had the lowest correlations with the fingerling survival traits recorded in freshwater.…”
Section: (Iii) Factors Causing Weak Correlations Between Life Stagesmentioning
confidence: 99%
“…33 Most of the animals could be included in the data analysis based on the separate presence of combined class I or combined class II alleles. However, when the material was analysed based on the combined presence of class I and class II alleles, only 97 of the 1200 animals complied with the inclusion criteria of more than 26 animals per group with identical genotype.…”
Section: Consequences Of Genetic Variation In Fishmentioning
confidence: 99%